Análisis citogenéticos en personas expuestas a radiaciones ionizantes - Espinoza, Marco (1993)
Cytogenetical findings in 18 cases of suspected overexposure to ionizing radiations are shown. Despite the fact that in almost every case a number of aberrations was described, it was possible the estimation of biological doses in only two of them. Six persona (students working with x-rays in a practice) received very localized, high doses in fingers and eyes because of the incredibly erroneous use of an X ray diffraction machine, being their biological doses to whole body not relevant at all. Typical radiation-induced chromosomal damage (which is useful for biological dosimetry) is the appearance of dicentric chromosomes, chromosomal rings and acentric fragments, but the greatest amount of cytogenetical abnormalities found in this group are chromosomal breaks and gaps, chromatid aberrations, translocations, deletions, and radial figures (grouped as "others" in Table 1). This led us to suppose a. high number of background chromosomal aberrations in this people, probably because of wrong application of radiation protection rules.